Design of a robot for simple assembly operations - Low, Kin Huat. (2008)
A cylindrical robot consists of three linear movements and a wrist of two degress of freedom is designed and buil to manoeuvre objects for simple tasks. The objects considered in the present work are those broad metal sheets used in factories.